Method comparison study of peripheral blood CD34+ count performed on an Abbott CELL-DYN Sapphire hematology analyzer versus flow cytometry reference procedure (modified ISHAGE) - Avecilla, Scott T. (Adv Cell Gene Ther, 2018)
INTRODUCTION: CD34+ cell enumeration is a critical parameter used to determine the timing of apheresis collections of hematopoietic progenitor cell products (HPC(A)). Automated hematology analyzers equipped with flow cytometry capabilities may be a solution to the problem of limited access to standard flow cytometry testing. METHODS: We compared CD34+ cell enumeration using a reference flow cytometry procedure employing modified International Society of Hematotherapy and Graft Engineering (ISHAGE) analysis with a hematology analyzer /flow cytometer hybrid (CELL DYN (CD)Sapphire) using a sequential gating analysis designed to emulate the ISHAGE gating strategy. RESULTS: CD34+ cell values obtained from the ISHAGE and CD Sapphire analysis were plotted and compared in a linear regression analysis which showed a high degree of correlation (R(2)=0.96). No statistically significant (p=0.53) differences in CD34+ cell enumeration values were observed between the flow cytometer and automated hematology analyzer using manual analysis schema. CONCLUSIONS: We have demonstrated that an automated hematology analyzer equipped with a flow module can provide CD34+ cell enumeration results in the peripheral blood for clinical decision algorithms without the need for a dedicated flow cytometry laboratory.